The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.3390/su14042471
|View full text |Cite
|
Sign up to set email alerts
|

A Structured Review of Emotional Barriers to WASH Provision for Schoolgirls Post-Disaster

Abstract: Pubescent girls face unique emotional barriers to returning to school after a disaster concerning water, sanitation and hygiene (WASH). This paper explores themes of WASH, gender violence, the lack of dignity and sense of shame arising from inadequate WASH facilities for girls in disaster settings. We conducted a structured literature review of 126 sources to investigate the emotional constraints facing pubescent girls concerning WASH in schools in Indonesia, a region prone to frequent disasters. Findings are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 76 publications
0
1
0
Order By: Relevance
“…27 This multidimensional approach is hinged on the need to urgently adopt a disaster management cycle and ethics to reduce the possible biopsychosocial effects on the affected population and most specially to reduce the morbidities and mortalities to the lowest possible level as shown by various humanitarian response investigators. [52][53][54][55] Generally, this paper revealed that the consequences and humanitarian response outcomes are more skewed towards women and children. It can further be seen that the gender with the highest population receiving humanitarian services across camps in the TCF-affected districts is females, confirming the higher proportion of female population in Malawi.…”
Section: Bmj Public Healthmentioning
confidence: 83%
“…27 This multidimensional approach is hinged on the need to urgently adopt a disaster management cycle and ethics to reduce the possible biopsychosocial effects on the affected population and most specially to reduce the morbidities and mortalities to the lowest possible level as shown by various humanitarian response investigators. [52][53][54][55] Generally, this paper revealed that the consequences and humanitarian response outcomes are more skewed towards women and children. It can further be seen that the gender with the highest population receiving humanitarian services across camps in the TCF-affected districts is females, confirming the higher proportion of female population in Malawi.…”
Section: Bmj Public Healthmentioning
confidence: 83%
“…Adolescent girls were selected as this study forms one component of a larger interdisciplinary project to foster resilient post-disaster recovery psychosocially and by improving water sanitation and hygiene (WASH) for girls. Girls were exclusively included in this wider project due to their vulnerability to adverse psychological outcomes and inadequate post-disaster WASH facilities (see [84]). Therefore, this is primarily a study of female conceptualisations.…”
Section: Participantsmentioning
confidence: 99%